Shifting Baselines The Past and the Future of Ocean Fisheries - Jackson, Jeremy B.C; Alexander, Karen E.; Sala, Enric (Island Press/Center for Resource Economics : Imprint: Island Press, 2011)
Shifting Baselines explores the real-world implications of a groundbreaking idea: we must understand the oceans of the past to protect the oceans of the future. In 1995, acclaimed marine biologist Daniel Pauly coined the term "shifting baselines" to describe a phenomenon of lowered expectations, in which each generation regards a progressively poorer natural world as normal. This seminal volume expands on Pauly's work, showing how skewed visions of the past have led to disastrous marine policies and why historical perspective is critical to revitalize fisheries and ecosystems.   Edited by marine ecologists Jeremy Jackson and Enric Sala, and historian Karen Alexander, the book brings together knowledge from disparate disciplines to paint a more realistic picture of past fisheries. The authors use case studies on the cod fishery and the connection between sardine and anchovy populations, among others, to explain various methods for studying historic trends and the intricate relationships between species. Subsequent chapters offer recommendations about both specific research methods and effective management. This practical information is framed by inspiring essays by Carl Safina and Randy Olson on a personal experience of shifting baselines and the importance of human stories in describing this phenomenon to a broad public.    While each contributor brings a different expertise to bear, all agree on the importance of historical perspective for effective fisheries management. Readers, from students to professionals, will benefit enormously from this informed hindsight.